Peran Koperasi Wanita dalam upaya Pemberdayaan Perempuan pada Koperasi Wanita di Kecamatan Blahbatuh Kabupaten Gianyar - Devanty, Cyntia Putri; Saskara, Ida Ayu Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 4, April 2017 (pp. 472 - 676), 2017)
Gianyar regency as one districts in the province of Bali, with the development of women's cooperatives is very rapid. In fact a lot of women's cooperatives are not active when the existence of women's cooperatives greatly help women belonging to economically weak. The purpose of this research is to analyze the role of women in the cooperative effort to empower women, the condition of the welfare of members of women's cooperatives, women's cooperatives and potential future. The study was conducted at the Women's Cooperative Blahbatuh. The research sample are 85 respondents to the sampling technique used was proportional random sampling. The study was descriptive research methods of observation and interviews. Research using descriptive statistical tests and SWOT analysis. Based on the results obtained by analysis concluded that the role of women's cooperatives in women's empowerment, especially for cooperative self running well, but for co-located at the village office still needs to be improved, livelihoods women's cooperatives relatively prosperous, and the potential of women's cooperatives foreseeable future have the opportunity which is quite large compared to the threat that would arise
Keywords: pemberdayaan; kesejahteraan; potensi; koperasi wanita